Case Report of Benign Breast Tumor: Fibroadenonma Mammae - Mahendra Mahendra; Zulhendry Zulhendry; Dina Ramsky; Dian Takwa Harahap (International Journal of Medicine and Health, 2024)
Fibroadenoma mammae is a benign breast tumor that occurs due to abnormal proliferation of periductal tissue into the lobules, often found in the upper lateral quadrant area due to the highest distribution of glands in this tissue. FAM is commonly experienced by younger women between the ages of 20-40 years, with a median age of 30 years. The clinical appearance of FAM lumps is typically lobulated, mostly 2-3 cm in diameter, with a firm and mobile consistency, without causing inflammatory reactions, skin dimpling, or nipple retraction. In this case, we report an 18-year-old female patient diagnosed with a breast tumor. The history revealed a lump in the left breast that enlarged within 1 month, initially the size of a marble and growing to the size of a quail egg, occasionally causing pain. On physical examination, the lump was palpable, mobile, without tenderness or signs of malignancy. Ultrasound examination showed signs of a benign tumor.